The Implementation of Ict Based Education in Elementary Teacher Education (PGSD) in Indonesia - Adie E. Yusuf (Humaniora, 2016)
In fact, Information Communication and Technology (ICT) have been utilized in schools even though relatively small in numbers. At present, there is a program for Elementary Teacher Education called PGSD program in Indonesia. The PGSD program is an in-service teacher training program especially for elementary school teachers in Indonesia, to improve their qualifications from Diploma-2 to Strata-1 level, conducted through ICT-based distance learning mode. This study uses survey method to examine the accessibility of ICT infrastructure and networks, and the effectiveness of using ICT for teaching and learning in six university member of PGSD program in Indonesia. The results of the study show that the PGSD program needs to improve the ICT infrastructure and networks as well as apply ICT based teaching and learning skills.